A lymphatic route for a hyperbranched heteroglycan from Radix Astragali to trigger immune responses after oral dosing. (15th September 2022) - Zhang, Quanwei; Li, Lifeng; Hao, Shuang; Liu, Man; Huo, Chuying; Wu, Jianjun; Liu, Hongbing; Bao, Wanrong; Zheng, Hongming; Li, Zhipeng; Cheng, Huiyuan; Fung, Hauyee; et al.
Abstract: Gut barrier makes a huge research gap between in vivo and in vitro studies of orally bioactive polysaccharides: whether/how they contact the related cells in vivo . A hyperbranched heteroglycan RAP from Radix Astragali, exerting antitumor and immunomodulatory effects in vitro and in vivo, is right an example. Here, we determined first that RAP's antitumor activity is immune-dependent. Being undegraded and non-absorbing, RAP quickly entered Peyer's patches (PPs) in 1 h where it directly targeted follicle dendritic cells and initiated antitumor immune responses. RAP was further delivered to mesenteric lymph node, bone marrow, and tumor. By contrast, the control Dendrobium officinale polysaccharide did not enter PPs. These findings revealed a blood/microbiota-independent and selective lymphatic route for orally administrated RAP to directly contact immune cells and trigger antitumor immune responses. This route bridges the research gap between the in vitro and in vivo studies and might apply to many other bioactive polysaccharides. Graphical abstract: Unlabelled Image